2007
DOI: 10.2967/jnumed.107.040428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SPECT/CT, SPECT, and Planar Imaging with Single- and Dual-Phase 99mTc-Sestamibi Parathyroid Scintigraphy

Abstract: Various methodologies for 99m Tc-sestamibi parathyroid scintigraphy are in clinical use. There are few direct comparisons between the different methods and even less evidence supporting the superiority of one over another. Some reports suggest that SPECT is superior to planar imaging. The addition of CT to SPECT may further improve parathyroid adenoma localization. The purpose of our investigation was to compare hybrid SPECT/CT, SPECT, and planar imaging and to determine whether dual-phase imaging is advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
178
5
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(196 citation statements)
references
References 22 publications
7
178
5
4
Order By: Relevance
“…This could be because patients who underwent DTDP imaging were patients who initially underwent DT imaging and findings from the initial Tc-99m sestamibi and Tc-99m pertechnetate images were deemed insufficient for diagnosis by the nuclear medicine physician on duty thus prompting further delayed imaging, so patients in the DTDP group represented 'difficult' patients which findings were likely to be inconclusive to begin with. Both add-on SPECT and SPECT/CT improved the diagnostic accuracy over planar imaging alone which concurs with previous studies [5,[16][17][18][19]28]. However, SPECT imaging appeared to have a higher diagnostic accuracy than SPECT/CT which is unexpected and contradicts a previous study which demonstrated the superiority of SPECT/CT over SPECT alone [29].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This could be because patients who underwent DTDP imaging were patients who initially underwent DT imaging and findings from the initial Tc-99m sestamibi and Tc-99m pertechnetate images were deemed insufficient for diagnosis by the nuclear medicine physician on duty thus prompting further delayed imaging, so patients in the DTDP group represented 'difficult' patients which findings were likely to be inconclusive to begin with. Both add-on SPECT and SPECT/CT improved the diagnostic accuracy over planar imaging alone which concurs with previous studies [5,[16][17][18][19]28]. However, SPECT imaging appeared to have a higher diagnostic accuracy than SPECT/CT which is unexpected and contradicts a previous study which demonstrated the superiority of SPECT/CT over SPECT alone [29].…”
Section: Discussioncontrasting
confidence: 49%
“…The dual phase (DP) protocol compares two or more Tc-99m sestamibi images obtained at Original different time points and diagnosis is based on the observation that Tc-99m sestamibi washes out of the thyroid more rapidly than from hyperfunctioning parathyroid lesions [15]. Tomographic imaging including single photon emission computed tomography (SPECT) and single photon emission computed tomography/computed tomography (SPECT/CT) has been suggested to provide improved diagnostic accuracy over planar imaging [16][17][18][19]. The purpose of this study was to determine the diagnostic accuracy of various nuclear medicine parathyroid imaging techniques for preoperative localization of hyperfunctioning parathyroid glands.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other conventional imaging modalities such as ultrasonogram (US), computed tomography (CT), and magnetic resonance (MR), 99m Tc-2-methoxy-2-methylpropyl isonitrile ( 99m Tc-sestamibi, MIBI) parathyroid scintigraphy has been shown to have higher sensitivity in detecting parathyroid adenomas [1,2]. In addition, the anatomical information provided by single positron emission computed tomography/computed tomography (SPECT/ CT) has improved the detection and localization of parathyroid lesions compared to planar scans alone [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the introduction of SPECT/CT has been advocated to more accurately localize parathyroid lesions (17,18). Further experience with SPECT/CT could show more benefits.…”
Section: Discussionmentioning
confidence: 99%